Ice age, current climate, habitat availability, and the diversity of European dragonflies and damselflies - Mónica Gómez-Vadillo; Joaquín Calatayud; Fernanda Alves-Martins; Cristina Ronquillo; Joaquín Hortal (Frontiers of Biogeography)
Several studies show that species richness patterns are determined by current climate and Pleistocene climatic oscillations. Additionally, habitat availability is an important driver of current species diversity, especially in aquatic ecosystems where lentic (standing water) and lotic (running water) habitats play distinct roles in species composition and richness. Odonates, an order of aquatic insects, exhibit distinct adaptive traits in response to climate and to lentic and lotic habitats. In this work, we study the species richness patterns of European odonates and the influence of past and current climate, and habitat availability. The study covers 124 species distributed across Europe (excluding Russia and all European islands except Great Britain and Ireland), divided into three groups: all odonates, lentic species, and lotic species. Notably, lentic species total 70% of the studied Odonata species, thus influencing overall species richness patterns. We analyzed their diversity in Northern and Southern Europe, divided according to the 0 °C Isotherm of the Last Glacial Maximum (21,000 years ago), using data on current and Last Glacial Maximum climate (temperature and precipitation), as well as on habitat data from land cover and hydrology GIS maps. Our results suggest that the species richness patterns of dragonflies and damselflies are largely determined by the water-energy balance, with temperature influencing the decline in richness towards the north and precipitation determining the decline towards the south. Past climate oscillations affect species richness in southern and northern Europe. Habitat availability also influences odonate diversity to a lesser extent, with a positive correlation between lotic species richness and their habitat availability. In contrast, lentic species richness showed a negative correlation with the availability of lentic habitats. Highlights We evaluate whether the variation of dragonfly species richness across Europe is determined by current climate, the climatic conditions during the last ice age, and the availability of freshwater habitats. Dragonfly species richness is higher in Central Europe and decreases both northwards and southwards from there. These variations are primarily determined by current and past climate, and to a lesser extent by habitat availability. Temperature determines the northward decrease in species richness, while the southward decrease is so by precipitation. The last ice age climate had a greater influence than current climate in northern Europe, while in southern Europe current climate has a greater influence, particularly for species related to standing water habitats. Species richness is higher in areas with more rivers and water courses, while the relationship with the availability of standing water habitats is more nuanced.